1984
DOI: 10.1530/acta.0.1050233
|View full text |Cite
|
Sign up to set email alerts
|

Plasma responses of pancreatic polypeptide, glucagon and insulin in normal and alloxan diabetic dogs, and their regional levels in the pancreas

Abstract: The plasma responses of pancreatic polypeptide (PP), glucagon (IRG) and insulin (IRI) after administration of beef soup were studied in normal and alloxan diabetic dogs kept in a poor metabolic state for 4 weeks, and their regional levels in the pancreas were determined and compared at the uncinate process, head, body and tail. The plasma PP levels of the diabetic dogs were significantly higher than those of the normal dogs and they increased after beef soup administration in both groups. The plasma IRG levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The IRG content was high in the gastric and splenic parts, and very low in the duodenal part. Similar findings were also reported in the canine pancreas ( Gingerich et al 1978;Tasaka et al 1984). Orci et al (1976) and Baetens et al (1976) found morphologically using the immunofluorescence technique that glucagon containing cells were abundant in the body and tail of the pancreas, and that, on the other hand, PP-containing cells were abundant in the head and scarce in the body and tail of the rat pancreas.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The IRG content was high in the gastric and splenic parts, and very low in the duodenal part. Similar findings were also reported in the canine pancreas ( Gingerich et al 1978;Tasaka et al 1984). Orci et al (1976) and Baetens et al (1976) found morphologically using the immunofluorescence technique that glucagon containing cells were abundant in the body and tail of the pancreas, and that, on the other hand, PP-containing cells were abundant in the head and scarce in the body and tail of the rat pancreas.…”
Section: Discussionsupporting
confidence: 79%
“…The contents of insulin and glucagon in the pancreas have been reported to be rich in the dorsal lobe compared with those in the ventral lobe (Wrenshall et al 1952: Orci andPerrelet 1981;Trimble et al 1982;Tasaka et al 1984). On the contrary, pancreatic polypeptide is abundant in the ventral lobe of the pancreas (Gingerich et al 1978;Gersell et al 1979;Orci and Perrelet 1981;Tasaka et al 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperglucagonemia and high glucagon content in the pancreas are found in streptozotocin diabetic rats together with a marked decrease in insulin in the pancreas (unpublished observations) and no significant increase in glucagon content in the pancreas of alloxan diabetic dogs was reported (Tasaka et al 1984). The histological findings in the pancreas of NOD mice would be different from those in animals with such experimental diabetes in that the destruction of the pancreatic islet is not limited to B cells.…”
Section: Discussionmentioning
confidence: 85%